HRCT Chest Findings of Re-expansion Pulmonary Edema: A Case Report - Koirala, Sapana; Shrestha, Om Kumar; Baral, Sharad Chandra (Nepalese Journal of Radiology, 2023)
Re-expansion pulmonary edema occurs when the lung re-expands after an extended duration of collapse. It is rare with the reported incidence between 0% and 1%. We present a case of a 51-year male who presented with breathlessness, cough and right-sided chest pain. Chest radiograph showed right-sided pneumothorax. After 2 hours of chest tube insertion, the patient developed tachypnea and severe hypoxemia. HRCT chest revealed consolidation, ground glass opacity and smooth interlobular septal thickening in the right lung as well as a small patch of ground glass opacity in the contralateral lung. The serial radiograph showed resolution of consolidation and ground glass opacities.